Peningkatan Hasil Belajar Mata Pelajaran IPA Melalui Media Power Point di Kelas IV - Listiya Anggraeny (Universitas Sebelas Maret, 2020)
This classroom action research aims to improve student learning outcomes in science material about natural resources and their preservation. This research is a classroom action research (PTK) which is carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the fourth grade students of SDN Bener 01 Majenang in the academic year 2020/2021, totaling 31 students. Data collection techniques using observation and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the application of power point media can improve student learning outcomes on Natural Resources and Conservation materials in grade IV SDN Bener 01 Majenang in the academic year 2020/2021 as evidenced by the percentage of completeness of learning outcomes in cycle I of 38.7% to 87% in cycle II and 100% in cycle III.